PTU-159 Characterisation of Oesophageal Muc1 Expression in the Progression to Oesophageal Adenocarcinoma. (4th June 2013) - Butt, M A; Oukrif, D; Haidry, R J; Rashid, M; Khan, S-U-R; Pye, H; Bloom, E S; Deonarain, M; Swallow, D; Banks, M R; Rodriguez-Justo, M; Novelli, M; et al.
Abstract : Introduction: Studies on oesophageal MUC1 expression have shown conflicting results. One found MUC1 in 100% of 52 oesophageal adenocarcinoma (OA) patient's using an anti-MUC1 antibody(1), whilst another found no expression in 23 OA cases at the RNA level(2). It is probable that detection of MUC1 repeat domains varies in the progression to cancer due to changes in glycosylation. This study aims to characterise oesophageal MUC1 expression using antibodies binding extracellular peptide repeats and an intracellular epitope unaffected by surface glycosylation. Methods: 138 paraffin embedded specimens were selected from 106 patients containing normal squamous (Sq; n = 34), normal gastric (G; n = 15), non-dysplastic Barrett's (NDBE; n = 27), low grade dysplasia (LGD; n = 22), carcinoma in-situ (HGD/IMC; n = 35) and invasive OA (IOA; n = 21). 11 IOA cases had matched specimens containing infiltrated lymph nodes (LN). Immunohistochemistry was performed using the antibodies CT2 (binding the MUC1 cytoplasmic tail)(3), NCL-MUC-1(binding the epitope PDTRPAP of the extracellular peptide) and HuHMFG1 (binding PDTR of the extracellular peptide). Intensity (0 to 3+) and extent (0; < 1% = 1; 1–10% = 2; 10–33% = 3; 33–66% = 4; > 66% = 5) of tissue staining was scored. Positive cases were defined as those staining 2+/3+ in > 10% of the pathology examined. Results: MUC1 was shown to be significantly expressed using our antibody panel (HuHMFG1; CT2; NCL-MUC-1) in Sq (61%; 38%; 40%), G (100%; 100%; 86%), NDBE (96%; 100%; 6%), LGD (91%; 86%; 12%), HGD/IMC (91%; 97%; 19%) and IOA (95%; 91%; 82%). 100% of the metastatic OA group with infiltrated LNs stained positively with HuHMFG1. Using internal MUC1 detection with CT2 for comparison, the sensitivity & positive predictive value for external MUC1 detection were 95%; 95% for HuHMFG1 and 40%; 93% for NCL-MUC-1. Conclusion: This study suggests MUC1 expression inferred by detection with HuHMFG1 and CT2, binding extra and intracellularly, increases early in progression to OA. The MUC1 epitope bound by NCL-MUC-1 appears later. This may be due to changes in glycosylation during progression. Therapeutic modalities targeting MUC1 may be applicable to the majority of patients with preneoplastic BE and OA. Disclosure of Interest: None Declared References: Piessen et al. J. Clin. Pathol.62, 1144–1146. Guillem et al. Int. J. Cancer88, 856–861. Courtosy of Prof. Sandra Gendler. Mayo clinic. USA.